Ataxia and Encephalitis in a Young Adult with EBV Mononucleosis: A Case Report - Rashid S. Hussain; Naaz A. Hussain (Case Reports in Neurological Medicine)
Neurological manifestations of mononucleosis are extremely rare, occurring in about 1% of all cases. However, when they occur, appropriate treatment must be undertaken to ensure appropriate symptomatic management and reduce morbidity. We present the case of a 25-year-old graduate student with weeklong complaints of fever, sore throat, fatigue, nausea, and “dizziness.” She later developed increased sleep requirements, ataxia, vertigo, and nystagmus with a positive EBV IgM titer confirming acute infectious mononucleosis. The patient was clinically diagnosed with EBV-associated cerebellitis and encephalitis, displaying neurological and psychiatric impairment commonly seen in postconcussion syndrome. MRI showed no acute changes. She was started on valacyclovir and a prednisone taper, recovering by the end of twelve weeks. Though corticosteroids and acyclovir are not recommended therapy in patients presenting with EBV-associated ataxia, clinicians may want to keep a low threshold to start these medications in case more serious neurological sequelae develop.